How does Fetal Autopsy after Pregnancy Loss or Termination for Anomalies and other Complications Change Recurrence Risk? - Arianna Cassidy; Claire Herrick; Mary E. Norton; Philip C. Ursell; Juan Vargas; Jennifer L. Kerns (Thieme Medical Publishers, Inc., 2019)
Abstract Objective Historically, fetal autopsy was common after terminations for anomalies. Previous studies report that fetal autopsy confirms ultrasound findings in the majority of cases. This study aims to examine correlation between prenatal and autopsy diagnoses at University of California, San Francisco (UCSF) and evaluate whether autopsy adds diagnostic information, specifically information that changes risk of recurrence for future pregnancies. Study Design We conducted a retrospective chart review of all fetal autopsies performed at UCSF between 1994 and 2009. Prenatal diagnosis was compared with autopsy diagnosis; for cases where there was a change in diagnosis, an MFM (maternal-fetal medicine specialist) reviewed the case to assign risk of recurrence before and after autopsy. Results Overall, there was concordance between prenatal diagnosis and autopsy diagnosis in greater than 91.7% of cases. Autopsy added information that resulted in a change in recurrence risk in 2.3% of cases (n = 9). Conclusion For the vast majority of cases, there is agreement between prenatal and autopsy diagnosis after pregnancy loss or termination for fetal anomalies. Only a small percentage of autopsies change recurrence risk. This may be useful when counseling women about method of termination and when counseling couples about whether to have an autopsy.